Does online incivility cancel out the spiral of silence? A moderated mediation model of willingness to speak out. (November 2021) - Masullo, Gina M; Lu, Shuning; Fadnis, Deepa
This study tested whether different negatively valenced emotional reactions—feeling angry or depressed—to incivility produce varying intentions to speak out. A related goal was to assess whether these emotional responses led to intentions to speak out regardless of whether one holds a minority or majority viewpoint. Results of an online experiment ( N  = 1126) showed that intentions to speak out varied based on the intensity of the emotional responses people had after being exposed to incivility. Specifically, when uncivil messages produced lower levels of either emotion—anger or depression—people were less likely to speak out, regardless of opinion climate. However, if emotional responses were more intense for either emotion, people were more likely to speak out, regardless of opinion climate.